Proposal for the hierarchical classification of thematic cartography methods and its application to evaluation of Czech and Slovak national atlases. (April 2019) - Miklín, Jan; Dušek, Radek
In this article, we review the classifications of thematic cartography methods and propose a new universal classification system, putting a special emphasis on the hierarchisation and logical structure. Basic groups of thematic cartography methods are defined as follows: (1) value-by-size/count, (2) value-by-colour, (3) dot density maps, (4) surfaces and (5) cartograms, with a further detailed classification. In the second part, we apply the proposed classification system on the evaluation of thematic cartography methods in five Czech and Slovak national atlases published throughout nearly a century. Our results show that the lowest number of methods was used in the oldest atlas (published in 1935), while the highest number of methods was used in the atlases from the years 1966 and 1980. The newest national atlases (published in 2002 and 2010) use a relatively low number of methods. The maps of the newest atlases are also simpler, and they contain a generally low amount of ascertainable information.